Fibrous Variant of Hashimoto's Thyroiditis as a Diagnostic Pitfall in Thyroid Pathology. (5th December 2013) - Iannaci, G.; Luise, R.; Sapere, P.; Coluccino, V.; Ronchi, A.; Faggiano, A.; Marotta, V.; Colao, A.; Spiezia, S.
Abstract : Fibrous variant of Hashimoto's thyroiditis is a rare condition occurring in about 10% cases, mainly middle age people. It is characterized by an extensive fibrous proliferation without extension into the surrounding structures. A 55-year-old female was referred to our department for an unexplained onset of cervical discomfort. She presented a voluminous goiter of hard consistence, dyspnea and dysphagia. Given the compressive symptoms and the non-diagnostic result of the biopsy, a total thyroidectomy was performed. Microscopically the thyroid parenchyma was characterized by broad bands of fibrosis with severe atrophy of thyroid follicles and lymphocytic inflammatory infiltrate distributed within and around the lobules. In view of the morphological and immunohistochemical findings, a diagnosis of HTFV was made. The fibrosclerotic process is the key feature of several thyroid diseases so that the clinician and the pathologist have to consider that many diagnostic pitfalls can occur in this field. The differential diagnosis between HTFV and RD is sometimes arduous due to the partial clinical and morphological overlapping and to the poor efficacy of conventional cytology as well as pre-surgical biopsy. Considering these features, histological examination is mostly mandatory.